Горленко Дмитро Лазарович (1660 – 1731) - Половець, В. (Сiверянський лiтопис, 2018)
У статті мова йде про одну з визначних постатей Чернігівщини, державного діяча
Гетьманської епохи, полковника Прилуцького полку, наказного гетьмана козацького
війська у Північній війні (1705), найближчого соратника Івана Мазепи. В статье речь идёт об одной из выдающихся личностей Черниговщины, государственном деятеле Гетьманской эпохи, полковнике Прилукского полка, наказном гетмане казацкого войска в Северной войне (1705), ближайшем соратнике Ивана Мазепы. D.L. Horlenko is a Ukrainian statesman of the Hetman epoch, the colonel of Pryluky regiment
(1692 – 1708), mandative hetman of the Cossack army of the Northern war (1705),
one of the nearest comrades-in-arms of hetman Ivan Mazepa.
D. Horlenko was born in the family of Pryluky colonel Lazar Horlenko. Life of his father
defined Dmytro’s destiny who received the position of colonel in 1692. He was an active
supporter of severance with Moscow. After death of I. Mazepa, together with general record
keeper P. Orlyk and nephew of the hetman Andrii Voinarovskyi (on April 05, 1710) he was
one of the candidates for the position of hetman from the Ukrainian Cossacks which was in
expulsion. When, in the result of the struggle against Petro І, the game of Ukrainian foremen
was over, P. Orlyk left to Sweden through Vienna with his company, and D. Horlenko had to
return to Kyiv in 1715. By the order of the imperial government, he was ordered to appear
in Moscow where he stayed till 1731. Having returned to Pryluky, D. Horlenko made his will
and he died the same year. He was buried in the family crypt of Hustynia monastery.